Mechanisms of Genomic Instability in Breast Cancer. Issue 7 (July 2019) - Duijf, Pascal H.G.; Nanayakkara, Devathri; Nones, Katia; Srihari, Sriganesh; Kalimutho, Murugan; Khanna, Kum Kum
Abstract : Breast cancer is the most common cancer among women globally. Genomic instability (GI) refers to the increased tendency to accrue genomic alterations. It drives heterogeneity and is a hallmark of cancer. Genomic integrity is closely guarded by several mechanisms, including DNA damage checkpoints, the DNA repair machinery, and the mitotic checkpoint. Alterations in these surveillance mechanisms cause GI. In breast cancer, several pathways maintaining genomic integrity are distinctly altered, including some that have been successfully exploited for therapeutic targeting. In this review, we comprehensively discuss the recent advances on the mechanisms of GI in breast cancer, highlighting DNA repair defects and chromosome segregation errors during mitosis. We further review the clinical implications and therapeutic potential of targeting GI in the era of precision medicine. Highlights: Breast cancer is characterized by vast genomic instability (GI)-driven heterogeneity, including mutations, copy number alterations, and chromosome structural rearrangements. GI is caused by defects in several mechanisms, including DNA damage repair, DNA replication, transcription, mitotic chromosome segregation, and telomere maintenance. Recent technological advances have spurred identification of novel GI mechanisms, including chromothripsis and its molecular/genomic consequences in breast cancer. Moreover, the recent observation that whole-genome doubling occurs in nearly half of all breast cancers suggests that tetraploidy is a primary intermediate step to aneuploidy in breast cancer development. The recent success of poly-ADP ribose polymerase inhibitors (PARPi) in selectively treating BRCA-deficient breast cancers has proven the potential of targeting GI in aggressive forms of cancer.